(untitled) (Research, Society and Development, 2021)
The objective was to raise, in national and international literature, as scientific evidence about occupational risk indicators and their reflexes for the health of the nursing team in a neonatal unit. Integrative review study, carried out during the month of October 2020. A search conducted through the Virtual Health Library portal, in the LILACS, MEDLINE, IBECS and BDENF databases, simultaneously, for articles in English, Portuguese and Spanish with abstract and full text available, published between 2015 and 2020. Duplicate articles, review, methodologically classified as thesis, dissertation or monograph as well as those that did not fit the theme were excluded. 15 publications were identified, of which, 5 met the eligibility criteria. As for occupational risk, it was identified: psychological damage: occupational stress; exhaustion; desire to quit work, emotional exhaustion, professional demotivation; physical damage: work overload; inadequate environmental conditions and noise; social damage: difficulties in interpersonal relationships and the need to restrict personal contacts. The reflexes on the worker’s health were: depression, frustration, anger, bitterness, negativity and compulsiveness; fatigue, exhaustion, lack of attention, low immunity; irritability, cynicism, low empathy. Occupational risks reflect negatively on the health of nursing workers. The strategy of prevention and control of these is recommended, seeking to promote a working environment in accordance with the principles of safety in force in the legislation.